SCIENCE OF HIPPOLOGICAL TERMS IN ENGLISH THEORETICAL BASICS - Аdinazarov Uktam Kushokovich (American Journals, 2023)
This paper presents a contrastive analysis of IT terminology in English and Uzbek. The study aims to identify the similarities and differences between the two languages in terms of their hippological vocabulary. And, we have analyzed the scientific and theoretical basis of English hippological terms and analyzed the specific features of some terms.
Keywords: termin, hippological terms, term is a linguistic unit, terminology.